Anglų kalbos interferencija antrosios JAV lietuvių kartos gimtosios kalbos tartyje - Pažūsis, Lionginas (Kalbotyra, 1988)
The present paper is an attempt to examine the Lithuanian spoken with an English accent by the second generation of Lithuanian immigrants in the USA and to describe the forms of phonic interference in the categories distinguished by Uriel Weinreich. The analysis shows that cases of under-differentiation of phonemes can be further subclassified into unilateral and bilateral. Certain additional factors inhibiting mispronunciation are also discussed.